Comparative study of pelvic floor displacement in a woman with stress urinary incontinence using finite element method and magnetic resonance imaging - Cristina Saleme (2009)
MRI has been used in the diagnostic evaluation of the pelvic floor dysfunctions. Static images show their morphology while dynamic images show the functional changes that occur on straining and contraction of the levator ani. With dynamic images, displacement of organs and pelvic floor muscles can be computed in three planes (axial, sagital and coronal) [1]. The purpose of this study is to compare pelvic floor muscle (PFM) displacement of a woman with stress urinary incontinence, produced during a voluntary PFM contraction, using magnetic resonance imagining (MRI) and the contraction activation methodology using Finite Element Analysis (FEA).